PENGARUH ANALISIS AKUNTANSI PEMBIAYAAN IJARAH PADA BAITUL QIRADH BAITURRAHMAN DI KOTA BANDA ACEH - Maisarah, Maisarah; Ibrahim, Ridwan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This is a qualitative research, in which the purpose of this study was to determine the accounting records Ijara financing at Bq Baiturrahman in Banda Aceh and to determine differences in the accounting records at the Ijara financing Baitul Qiradh Baiturrahman in Banda Aceh as well as with PSAK 107.The location was done at Baitul Qiradh Baiturrahman in Banda Aceh, while the type of research that is used by the author in this study is descriptive case study approach. The data collection was conducted in order to obtain or collect data (information) that can explain or answer the problems of research in question objectively. The data collection was done by using dokuemntasi and interview and literature study.The results of this study explains that asset into Ijarah assets, the product morgate be directly into customers' legally and maintenance costs related to assets that are Ijara-kan sepenuhya borne by the customer. Application of the financing with the contract of Ijarah at Baitul Qiradh Baiturrahman, as a whole is in conformity with the National Sharia Board Fatwa number 27 on Ijarah but charging of maintenance on the assets handed over entirely to the customer, then the accounting treatment of financial transactions in the financing of the contract of Ijarah muntahiya bittamlik at Baitul Qiradh Baiturrahman as a whole is not in accordance with PSAK 107, except that there is an account that does not exist in PSAK 107, namely the elimination of receivables earning assets, while the variation in the IAS with Baitul Qiradh Baiturrahman happen in practice in the field is the naturally happened, saw the development of sharia accounting until now still in the developmental stage and continues to experience reforms.Keywords: Accounting Records Ijarah Financing.